Surface-enhanced Raman scattering (SERS) spectroscopy platforms for enhanced detection at the nanobio interface: from metabolites to microorganisms - Leong, Shi Xuan (Nanyang Technological University, 2023)
Surface-enhanced Raman scattering (SERS) spectroscopy is a powerful spectroscopic technique that enhances molecules’ weak Raman signals for ultrasensitive identification and quantification. However, molecule detection at the nanobio interface is hindered by challenges including poor surface affinities, complex sample matrices, and analogous chemical structures. In this thesis, we overcome these roadblocks by synergizing designer plasmonic platforms with emerging strategies to expand the analyte scope, ranging from small-molecule metabolites to microorganisms. Here, we successfully design direct enantiospecific nanoparticle-analyte interactions for label-free, generic chiral differentiation. We also leverage pattern-based recognition of differential probe-analyte interactions to distinguish small-molecule metabolites, both as individual molecules and in complex mixtures, such as the human breath, as well as microorganisms with complex surface biomolecular architectures. We thus showcase the immense potential of the novel and strategic combination of various techniques in advancing SERS beyond the current state-of-the-art toward real-life detection of a broader analyte scope.